Forecasting Mango and Citrus Production in Nigeria: A Trend analysis (2007)
This paper provides the prediction of future production of citrus and mango in the medium term up to 2010. The prediction was based on the assumptions that past trends (area planted and yield) and existence of normal weather pattern will hold. Time trend model with specific emphasis on growth model was employed. The analysis delineated three different eras (period between 1961and 2003, 1986 – 2003, and 1991-2003). These eras were used to simulate the different policy regimes of Regulation, Structural Adjustment era and Liberalization era. In general, output of citrus and mango maintained upward trend over the years. However, the growth rate was highest for the era including Structural Adjustment. Following from this, output predictions over the medium term are highest for the analysis with Structural Adjustment era